IsoArcH.eu: An open-access and collaborative isotope database for bioarchaeological samples from the Graeco-Roman world and its margins. (June 2018) - Salesse, Kevin; Fernandes, Ricardo; de Rochefort, Xavier; Brůžek, Jaroslav; Castex, Dominique; Dufour, Élise
Abstract: This paper describes IsoArcH, a new web-based database of isotopic data for bioarchaeological samples from the Graeco-Roman world and its margins. IsoArcH was designed as a cooperative platform for the dissemination of isotopic data and associated archaeological information. IsoArcH follows the open access model and is freely accessible online (http://www.isoarch.eu ). Created for paleodietary, paleomobility and paleoenvironmental reconstruction research purposes, IsoArcH compiled to this day published isotopic data for human, animal, and plant remains, as well as organic residues, from nearly 300 sites. All data have been georeferenced allowing for their display on ancient world maps and placement into their contemporaneous geopolitical background. In this paper, several data-driven examples are shown to illustrate the research potential offered by IsoArcH.